2005
DOI: 10.1213/01.ane.0000145065.20816.b5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexmedetomidine on Left Ventricular Function During Hypoxia and Reoxygenation in Isolated Rat Hearts

Abstract: Hypoxia resulting from apnea in patients with sleep apnea is an important factor in heart disease. We designed the present study to determine whether dexmedetomidine (DEX) has a direct protective effect against hypoxia-reoxygenation-induced left ventricular dysfunction without systemic hemodynamic and humoral effects. Isolated rat hearts were exposed to 60-min hypoxia followed by 30-min reoxygenation with 0, 10, or 100 nM DEX prehypoxia administration (n = 7 each group). In a second experiment (n = 7), 100 nM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
0
15
1
1
Order By: Relevance
“…However, previous studies have reported that administration of dexmedetomidine after reperfusion did not exert a direct protective effect on left ventricular dysfunction, and even increased myocardial infarct size in isolated rat hearts (13,43). Contrary to our secondary hypothesis, the results of the present study indicated that postconditioning with dexmedetomidine was also able to attenuate H/R injury of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 82%
“…However, previous studies have reported that administration of dexmedetomidine after reperfusion did not exert a direct protective effect on left ventricular dysfunction, and even increased myocardial infarct size in isolated rat hearts (13,43). Contrary to our secondary hypothesis, the results of the present study indicated that postconditioning with dexmedetomidine was also able to attenuate H/R injury of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 82%
“…Intracisternal administration of dexmedetomidine has prevented the rise of plasma norepinephrine, blocked the electrocardiographic abnormalities and preserved cardiac function in a rat model of intracranial hypertension [23]. Dexmedetomidine also exerts direct protective effect on left ventricular dysfunction caused by hypoxia-reoxygenation in rats [24] and decreases airway reactivity [25]. Intraperitoneally administered dexmedetomidine significantly decreased neuronal damage in a mice model of perinatal excitotoxic brain injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine was another agent searched in our study which has an alpha-2 adrenoceptor agonist effect and its effect on preventing I/R injury on several brain and heart I/R models were via decreasing the cathecolamine release during the ischemia period [5,6,30]. Hoffman et al have produced cerebral ischemia on rat brain model and observed that the neurological and histopathological results on the dexmedetomidine group was better than the control group and this effect was returned by using alpha-2 adrenoceptor antagonists [31].…”
Section: Discussionmentioning
confidence: 99%
“…Its proven that each molecule of propofol can scavange two free radicals and prevent the lipid peroxidation inducted by oxidative stress [3,4]. The alfa 2 adrenoreceptor agonist dexmedetomidin used as an anxiolytic and sedative agent in intensive care units decreases the cathecolamine decharge inducted by ischemia and decreases the damage caused by reperfusion [5,6].…”
Section: Introductionmentioning
confidence: 99%